Building software for simulation : theory and algorithms, with applications in C++ - Nutaro, James (Hoboken, N.J. : Wiley, 2011)
"This book offers a concise introduction to the art of building simulation software. It clearly demonstrates the five skills necessary for building simulations of complicated systems: abstractions for simulation dynamic systems; basic simulation algorithms for continuous and discrete event simulations; combining continuous and discrete event simulations into a coherent whole; strategies for testing a simulation; and theoretical foundations of the modeling constructs and simulation algorithms. This is indispensable reading for software programmers, developers, and engineers, and students in related courses"--Provided by publisher
"This book will be used as an introduction to the design and implementation of simulation software, as a reference for fundamental abstractions that are useful when building object-oriented simulation programs, and as a collection of specific algorithms for simulating dynamic systems"--Provided by publisher
Frontmatter -- Introduction -- First Example: Simulating a Robotic Tank -- Discrete-Time Systems -- Discrete-Event Systems -- Hybrid Systems -- Applications -- The Future -- Appendix A: Design and Test of Simulations -- Appendix B: Parallel Discrete-Event Simulation -- Appendix C: Mathematical Topics -- References -- Index.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Computer simulation; C++ (Computer program language); Digital computer simulation; Simulation par ordinateur; C++ (Langage de programmation); simulation; COMPUTERS -- Programming Languages -- 2 -- isacsh; COMPUTERS -- Programming Languages -- Java; COMPUTERS -- Programming Languages -- Pascal; Digital computer simulation; C++ (Computer program language); Computer simulation